2017
DOI: 10.3727/154427217x14858894687432
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Perceived Quality, Value, Satisfaction, and Destination Loyalty in Shiogama, Japan

Abstract: This study examines the relationships between perceived quality, value, visitor satisfaction, and loyalty in a new context—Shiogama, Japan—a seaside town with a population of 55,000 residents that is famous for its cultural attractions and attracts over 2 million visitors per annum. Drawing on theories from tourism, marketing, and destination management, we hypothesize that perceived quality of destination attributes, as well perceived value of the experience, will have a direct positive effect on tourist sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Customer satisfaction is usually studied as a unidimensional construct that measures overall satisfaction with the service organization, which is the result of a combined judgment of all interactions with the organization (El-Adly, 2018). Matsuoka et al (2017) find that an increase in travelers' perceived value of a destination increases satisfaction. Lu and Wang (2020) find that, from the travel perspective, an increase in travelers' perceived value increases customer satisfaction to some extent.…”
Section: Perceived Valuementioning
confidence: 83%
“…Customer satisfaction is usually studied as a unidimensional construct that measures overall satisfaction with the service organization, which is the result of a combined judgment of all interactions with the organization (El-Adly, 2018). Matsuoka et al (2017) find that an increase in travelers' perceived value of a destination increases satisfaction. Lu and Wang (2020) find that, from the travel perspective, an increase in travelers' perceived value increases customer satisfaction to some extent.…”
Section: Perceived Valuementioning
confidence: 83%
“…For example, a study conducted by , Sun et al (2013) and Rajaratnam et al (2014) showed that customers who have positive perception of value for money can cause customer satisfaction. Furthermore, several recent studies (Hallak, Assaker & El-Haddad, 2018;Sato, Gipson, Todd, & Harada, 2018;Matsuoka, Hallak, Murayama, & Akiike, 2017) found that perceived value has a significant impact on tourist satisfaction. In addition, empirical research disclosed that perceived value has positive impact on both future behavioural intentions and behaviours (Chen and Tsai, 2007).…”
Section: Perceived Valuementioning
confidence: 99%
“…Examples of items used by Matsuoka et al (2017) to measure destination service quality involve "Tourist's perception of cost benefit of travel", "Tourist's perception destination's restaurants", "Tourist's perception destination's atmosphere" and "Tourist's perception of souvenirs". Many studies used SERVQUAL to measure service quality, this scale includes five dimensions: Tangibles, reliability, responsiveness, assurance and empathy (Parasuraman et al, 2002;Gustafsson et al, 2005).…”
Section:  Destination Service Quality Dimensionsmentioning
confidence: 99%
“….1. Research model Source: Based on Murphy et al (2000), Chen and Tsai (2007), Chen and Chen (2010), Yuksel et al (2010), Song et al (2011), Qu et al (2011), Al-Ababneh (2013), Ramseook-Munhurrun et al (2015), Tsaur et al (2016), Jani and Nguni (2016), Prayogo and Kusumawardhani(2016),Matsuoka et al (2017) ,Sangpikul (2017) andMolina and Ochoa (2018).…”
mentioning
confidence: 99%